2021
DOI: 10.1002/app.52106
|View full text |Cite
|
Sign up to set email alerts
|

Modification of poly(butylene succinate) with biodegradable glycolic acid: Significantly improved hydrolysis rate retaining high toughness property

Abstract: Marine microplastic pollution damages the marine biodiversity and endangers human health. Poly(butylene succinate) (PBS) is considered a biodegradable polyester; however, PBS has a slow degradation rate in seawater. In this research, glycolic acid (GA) segments were introduced in PBS main unit via melt polycondensation. The number-average weight of PBSGA copolymer ranged from 3.1 to 4.1 Â 10 4 g mol À1 with GA contents of 0%-40%. PBSGA possessed excellent mechanical properties and thermal stability. The tensil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 34 publications
(56 reference statements)
0
8
0
Order By: Relevance
“…In our previous work, salt may inhibit the hydrolysis of PBSGA copolymer, but in this paper, salt have an accelerating effect may because polyether esters are more hydrophilic. This phenomenon was not significant 31,32 …”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…In our previous work, salt may inhibit the hydrolysis of PBSGA copolymer, but in this paper, salt have an accelerating effect may because polyether esters are more hydrophilic. This phenomenon was not significant 31,32 …”
Section: Resultsmentioning
confidence: 82%
“…This phenomenon was not significant. 31,32 It is very interesting that the weight loss of copolymer in acid and alkaline solution was completely different. For PBS copolymers, the weight loss in acid after 49 days was 6.4%, but the weight loss of PBSD60 copolymer was 98.6%.…”
Section: Degradation Behaviors Of Pbsd Copolymersmentioning
confidence: 99%
“…Yue Ding et al introduced GA units into the PBS homopolyester. The research results proved the increase in GA content improved the degradation rate of copolymer in acidic and neutral solution [ 49 ]. As shown in Figure 6 , the GA units were beneficial for hydrophilicity.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Scheme 1, PNST copolymers were synthesized by the melt‐polycondensation method 26,32 . The PNST copolymers were obtained and named PNST x which x was the molar content of NT in the copolymers.…”
Section: Methodsmentioning
confidence: 99%
“…The molecule weight decreased by more than 90%, and the mechanical strength and elongation at break were insignificant after 30 days. Hu 25 and Ding 26 further found that PBSG copolymers had excellent degradability in other water environments, including acidic, neutral, and alkaline solutions.…”
Section: Introductionmentioning
confidence: 97%